Implementasi “Educaplay: Froggy Jumps” dalam Meningkatkan Minat Belajar Siswa di SMP Negeri 2 Sukodadi - Putri Nur Alfianti, Thania; Muchamad Suradji; Zuli Dwi Rahmawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research intends to illustrate how the implementation of Educaplay: Froggy Jumps media is used to foster students' desire to learn in PAI subjects in grade VII C SMP Negeri 2 Sukodadi. The background of this research stems from the low interest of students in learning PAI lessons which tend to be monotonous due to conventional learning methods. Froggy Jumps was chosen because it is digital-based and has interactive features that appeal to students. This research uses a descriptive qualitative approach. Data collection techniques include observation, interviews, documentation. Data analysis is carried out through the process of data reduction, data presentation, and inductive conclusion drawn. Research results show that Froggy Jumps can increase students' interest in learning. Students appear more focused, active, and enthusiastic during learning. Features such as attractive visual displays, sound effects, scores, leaderboards, and deadlines provide more impressive, challenging, and less boring learning conditions. The responses of students and teachers show that Froggy Jumps is able to increase student attention, interest, and active engagement. Therefore, Educaplay: Froggy Jumps is effectively used as a learning medium to increase students' interest in learning, especially in Islamic Religious Education lessons. Keywords: Educaplay: Froggy Jumps, learning media, learning interest, PAI